2013
DOI: 10.1007/s12161-013-9691-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Shiga Toxin-Producing and Enteropathogenic Escherichia coli Serotypes O157 and O26 in Bulk Raw Milk

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media New York. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
8
1
2
Order By: Relevance
“…However, our model inputs show two main sources of uncertainty, namely the level of milk contamination and the probability of boiling milk. Firstly, the STEC O157:H7 concentration is uncertain and few studies are available in the literature, so we used the Italian study by Trevisani et al (2013) to better fit the STEC O157:H7 concentration in milk. Secondly, the probability of boiling milk was used in the model as 'scenario' analysis because this point was considered crucial for risk results and several studies reported very different percentages of consumers boiling milk (Giacometti et al, 2012b(Giacometti et al, , 2013Ricci, 2012;Crotta et al, 2016a, b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our model inputs show two main sources of uncertainty, namely the level of milk contamination and the probability of boiling milk. Firstly, the STEC O157:H7 concentration is uncertain and few studies are available in the literature, so we used the Italian study by Trevisani et al (2013) to better fit the STEC O157:H7 concentration in milk. Secondly, the probability of boiling milk was used in the model as 'scenario' analysis because this point was considered crucial for risk results and several studies reported very different percentages of consumers boiling milk (Giacometti et al, 2012b(Giacometti et al, , 2013Ricci, 2012;Crotta et al, 2016a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the positive samples resulted contaminated below the quantification limit (LOQ) of MPN‐PCR methods were equal to the value of 0.3 MPN/ml, the limit of quantification of the MPN‐PCR methods used (LOQ), the mean concentration measured by Trevisani et al. () was equal to 0.364 MPN/ml with a SD of 3.056. Considering the few amount of available quantitative data and with an apparent prevalence of 0.15%, no unbiased fitting methods could be applied to any probabilistic distribution, even considering recently proposed Markov chain Monte Carlo fitting methods (Williams et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of STEC in raw milk is estimated to 13.6% (Douëllou et al, ; Farrokh et al, ). Furthermore, infections can be associated with milk and products made from raw, filtered, and unpasteurized milk, such as cheeses (Álvarez‐Suárez et al, ; A. Gill & Oudit, ; Ivbade, Ojo, & Dipeolu, ; Jackson et al, ; Madic et al, ; Nobili et al, ; M Trevisani et al, ; Trevisani, Mancusi, Riu, & Serraino, ). Transmission route to milk mainly concerns the fecal contamination of unpasteurized milk that is particularly correlated with the fecal excretion of STEC strains.…”
Section: Introductionmentioning
confidence: 99%